PENGARUH MEDIA ULEAD VIDEO TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA PGRI GELUMBANG - Ika Wulandari; Yulia Djahir; Deskoni Deskoni (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This study aims to determine the effect of Media Ulead Video Knowledge Technologi the Learning Outcomes of Students Lesson In Economics in SMA PGRI Gelumbang. Research conducted experiments with this type of research is the design of the Pre-Experimental Design One-Group Pretest form-posttest design is using pretest and posttest with as much as 5 treatment sessions. The population is the entire class X consisting of 4 classes second semester of the school year 2013/2014, amounting to 143 people. By using random cluster sampling technique derived class X.4 as an experimental class treated media Ulead Video .Data collection techniques was obtained by using tests and observation. Statistics were used to analyze the data in a statistical parametric verification is through hypothesis testing (t-test) using t-test formula product moment and the significance level (α) = 5% and df = n-2 so (df =30 -2 = 28). The results of hypothesis testing using t-test obtained tcount ttable 2,473 while 1,714. thus the hypothesis proposed in this study can diterime truth, that there are influences learning media ulead video Content Knowledge of the learning outcomes of students in the subject of economics at SMA PGRI Gelumbang. Its influence can be seen in the comparison of learning outcomes of students in the experimental class with a mean pretest and posttest by by 76.2. That mean media ulead video. Therefore, it is advisable for teachers to implement instructional media ulead video as an alternative to improve the learning outcomes of students.